2005
DOI: 10.1002/ep.10075
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and absorption of nitric oxide in a packed tower with sodium hypochlorite aqueous solutions

Abstract: The oxidation and absorption of nitric oxide (NO) with sodium hypochlorite aqueous (NaClO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…More S 22 ions are dissociated from Na 2 S solution at pH 9 than that at neutral or acidic conditions. The dominating reactions of NO 2 absorption are reactions (1) and (2). The study also indicated that NO 2 absorption is most likely through hydrolysis of N 2 O 4 as presented in reactions (5).…”
Section: Process Chemistrymentioning
confidence: 71%
See 1 more Smart Citation
“…More S 22 ions are dissociated from Na 2 S solution at pH 9 than that at neutral or acidic conditions. The dominating reactions of NO 2 absorption are reactions (1) and (2). The study also indicated that NO 2 absorption is most likely through hydrolysis of N 2 O 4 as presented in reactions (5).…”
Section: Process Chemistrymentioning
confidence: 71%
“…Two-stage chemical scrubbing systems are designed to oxidize NO in the first stage and absorb the NO 2 in a second stage. In the first stage, the slow oxidation reaction of NO in air can be promoted by injecting strong oxidizing agents such as ozone (O 3 ), chlorine dioxide (ClO 2 ), or chlorine (Cl 2 ) into the flue gas, or adding an oxidant such as sodium chlorite (NaClO 2 ), hydrogen peroxide (H 2 O 2 ), sodium hypochlorite (NaClO) [2] to the scrubbing solution.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, NO x are mostly emitted as NO and, due to its poor solubility, wet-adsorption must be promoted by adding an oxidant that forms NO 2 , thus promoting NO x solubility [24][25][26][27]. Whereas such an approach is in principle possible, it must be noted that on-board storage of chemicals is undesirable due to both space/volume constrains and security issues.…”
Section: Introductionmentioning
confidence: 96%
“…But a feasible method is to oxidize NO to other soluble NO x species (NO 2 , N 2 O 3 , N 2 O 4 , N 2 O 5 , etc.). For this purpose, various oxidants such as hydrogen peroxide (H 2 O 2 ) (Liu and Zhang 2011), potassium permanganate (KMnO 4 ) (Chu et al 2001a), peracids (Littlejohn and Chang 1990), ferrous-chelating agents (Wang et al 2007; Yan et al 2015), sodium hypochlorite (NaClO) (Chen et al 2005) and sodium chlorite (NaClO 2 ) (Deshwal et al 2008; Wei et al 2009b) have been investigated to enhance the NO removal efficiency of the scrubbing solution. Among these oxidants, NaClO 2 has been found one of the most promising chemicals for NO oxidation.…”
Section: Introductionmentioning
confidence: 99%